Immune Evasion Strategies of Trypanosoma brucei within the Mammalian Host: Progression to Pathogenicity - Stijlemans, Benoît; Caljon, Guy; Van Den Abbeele, Jan; Van Ginderachter, Jo A.; Magez, Stefan; De Trez, Carl (Frontiers in Immunology, 2016)
The diseases caused by African trypanosomes are of both medical and veterinary importance and have adversely influenced the economic development of sub-Saharan Africa. Moreover, so far not a single field applicable vaccine exists, and chemotherapy is the only strategy available to treat the disease. These strictly extracellular protozoan parasites are confronted with different arms of the host’s immune response (cellular as well as humoral) and via an elaborate and efficient (vector)-parasite-host interplay they have evolved efficient immune escape mechanisms to evade/manipulate the entire host immune response. This is of importance, since these parasites need to survive sufficiently long in their mammalian/vector host in order to complete their life cycle/transmission. Here, we will give an overview of the different mechanisms African trypanosomes (i.e. T. brucei as a model organism) employ, comprising both tsetse fly saliva as well as parasite-derived components, to modulate host innate immune responses thereby sculpturing an environment that allows survival and development within the mammalian host.